BOOK REVIEW: FLORINA ILIS, “ROMANUL JAPONEZ ÎN SECOLUL AL XX-LEA” [THE JAPANESE NOVEL IN THE 20ᵀᴴ CENTURY], CLUJ-NAPOCA: PRESA UNIVERSITARĂ CLUJEANĂ, 2022, 225 P. - TUDORICĂ, Ioana-Ciliana (Studia Universitatis Babeș-Bolyai Philologia, 2022)
In recent years, a continuous interest for Japanese culture, language, values and literature can be noticed in the West, including in Romania. With numerous Japanese writers becoming the favourite authors of numerous people, a desire to understand Japanese literature on a deeper level can be felt. The volume The Japanese Novel in the 20th Century comes as a response to the need for exploring the development of Japanese literature, as it provides the readers with all the necessary information on the literary trends and their progress in the 20th century.